Efektivitas Penggunaan Media Kerangka Cerita Untuk Meningkatkan Kemampuan Menulis Teks Cerita Fantasi Pada Siswa SMP - Syarifatul Musyarofah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to determine the effectiveness of using story framework media in improving the ability to write fantasy story texts for class VII students at Junior high school 5 Cimahi. Writing fantasy story texts requires creativity, developing imagination, and the ability to organize story lines well. Based on initial observations, many students still have difficulty writing structured, creative and coherent fantasy stories. This research uses a qualitative descriptive method to describe the facts that emerged during the research through observation and questionnaires. Data was collected through observation sheets which included plot development, characterization, use of language, and creativity. Based on the results of the analysis, 39% of students achieved the Very Good category, 50% the Good category, and 11% the Poor category with an average score of 81.9, which is classified as Good. Thus, story framework media is effective in helping students develop better and more structured fantasy story text writing skills. It is hoped that this research can contribute to the development of more innovative and effective Indonesian language learning methods